Information Support for the Land Registration: Directions for Upgrading of Statistical Reporting - Nechyporuk, N. V. (Statistics of Ukraine, 2018)
Decentralization of power and rapid expansion of local self-governance in Ukraine, gradual extension of property forms and rights for land use determine the need for gradual reformation of the processes involved in land records and respective presentation of data in financial and statistical reports of business entities. The article is devoted to elaboration is issues relating to statistical recording of transactions with land resources. Results of the study show the decreasing number of forms of statistical reports on land resources. A comparative assessment of the forms of statistical and administrative reports for recording quantitative data on lands is made. Use of statistical reports on land resources and administrative reports on quantitative data on lands lays the grounds for monitoring of land use relations in Ukraine. Common and distinctive features of the statistical and administrative reports are found out by the results of the comparative analysis. The pressing issues in collecting statistical data on land market and land relations are outlined: the need in filing the data on the land value depending on land size, land owners and users, purpose of land; the need for filing the data on contracts for land purchase and sale and sale price (except for agricultural lands, due to the existing moratorium on their sales); the filing of data on the rental value of 1 acre of land by location, quality and purpose of land. The need for filing the statistical data on quality status and use of land recourses in business entities’ operation is demonstrated. Recommendations on improving statistical reports on land resources through introducing the annual statistical form “The Report on Land Status and Effectiveness of Land Use” are given. If applied, the proposed report will enable for build the integrated databases on quantity and quality of land resources.